Vodogradbeni protipoplavni ukrepi za varstvo pred škodljivim delovanjem hudourniških poplav kot sestavni del obvladovanja poplavnega tveganja - Trobec, Tajan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2011)
Structural measures play an important role in flood risk management. Their usage enables us to manage a certain part of flood risk. Their main purpose is to reduce flood hazard on flood-prone areas that have been inhabited or used for different human activities. The paper presents some of most common structural measures which serve for flash flood protection, the basic principle of operating, its advantages and disadvantages, as well as their environmental impact.
Keywords: floods; fluvial erosion; hidrogeografija; hudourniki; hydrogeography; naravne nesreče; natural disasters; poplave; rečna erozija; Slovenia; Slovenija; zaščita